Seamless incorporation of artificial water channels in defect-free polyamide membrane for desalination of brackish water - Yingsong Liu; Xieyang Xu; Chenshuo Wang; Huijun Yu; Weiyi Wang; Yanxi Gong; Changwei Zhao; Jianbing Wang (Nature Communications)
Abstract Artificial water channels (AWCs) show the potential for overcoming the permeability-selectivity tradeoff of polyamide (PA) membranes. However, the availability of biomimetic materials and limitations posed by fabrication-induced defects make the development of AWC-PA membranes a daunting task. Herein, we synthesize imidazolylethyl-ureidoethyl-phenyl (IUP) compounds to form AWC by self-assembling and provide a strategy to seamlessly incorporate AWC in defect-free PA membranes. IUP compounds are molecularly designed with enhanced nature to form AWC due to π-π stacking interactions. In addition, nanosized colloid AWC aggregates can be obtained in water directly with the aid of sodium dodecyl sulfate (SDS) and conveniently incorporated into PA layers. The AWC not only promotes the preferential selective passage of water but also exhibits good compatibility with the surrounding PA matrix. The biomimetic membranes demonstrate a water permeance of 4.3 L·m−2·h−1·bar−1 and NaCl rejection of 99.3%, much higher than that observed with marketed state-of-the-art membranes. Mechanism understanding reveals that the compatible interaction between AWC, SDS and PA matrix is a necessary requisite to fabricate defect-free AWC-PA layers. This strategy can be easily extended to industrial scale and the biomimetic membranes may represent the development direction of the next generation of high-performance reverse osmosis membranes.